Director selection in agricultural cooperatives—The process and the roles in the Finnish context - Kari Huhtala; Pasi Tuominen; Terhi Tuominen (Cogent Business & Management, 2020)
Director selection is linked with contradictory board roles which call for the need of multiple approaches. In cooperatives, which are member- and user-driven rather than profit-driven, this approach is essential. The aim of this study is to analyze director selection in agricultural cooperatives by using a qualitative approach and hence, contribute to theory development. The results indicate that the director selection process and roles contain several paradox issues in two dimensions: administrative culture as well as the roles and authority of important actors. The paper contributes to the understanding of (1) mechanisms and relationships inherent in the process of director selection in agricultural cooperatives (2) the administrative culture as well as the roles and authority of the actors in the process and (3) paradoxes which help us to understand tensions in director selection under the requirement of fulfilling both the performance task and the conformance task. The paper discusses the results against the current board theories and suggests a new paradox dimension. It is suggested that director selection should be studied further from the perspectives of (1) implications of the use of authority and (2) the implications of the administrative culture.
Keywords: 650; director selection; agricultural cooperative; board; governance; paradox